On Joint Distribution of General Dirichlet Series - Genys, J.; Laurinčikas, A. (Nonlinear Analysis: Modelling and Control, 2003)
In the paper a joint limit theorem in the sense of the weak convergence in the space of meromorphic functions for general Dirichlet series is proved under weaker conditions as in [1].